Implementasi Manajemen Sekolah untuk Meningkatkan Mutu Pendidikan di Tingkat Sekolah Menengah Pertama (SMP) - Efriani Efriani; Nur Ahyani; Ahmad Hussein Fattah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The purpose of this study was to find out how to describe the implementation of school-based management (SBM), how to improve the quality of education through school-based management, as well as the supporting and inhibiting factors in the implementation of school-based management. This study uses a qualitative approach with a descriptive method. Data collection techniques in this study are interview techniques, observation techniques and document study techniques. The subjects and informants in this study were the principal, vice principal, head of administrative officer, and the community. The data obtained in the field were analyzed by means of data reduction, data presentation and finally conclusions. The results obtained: (1) The implementation of school-based management at SMP Negeri 4 Abab can be said to be running well. (2) In the process of implementing SBM at SMP Negeri 4 Abab, namely the first input at this stage the principal makes a program implementation plan through deliberation involving all interest groups. The second stage of the process, in this stage the implementation of what was previously planned. Finally, the output or result of the SBM implementation process is to produce students with high achievements and to improve the quality of education. (3) The supporting factor in implementing SBM in SMP Negeri 4 Abab is that there is support from teachers, administrative officer and the community, both in the form of personnel and financial support. While the inhibiting factors are the people who are indifferent, lack of funds and inadequate facilities and infrastructure.